Financial ratio method peruvian listed companies - Farfan, Kurt Burneo (2017)
This document explains in a simple form the principles related to the calculation and interpretation of the financial ratio analysis, the formulas of the different kinds and the importance in the day-to-day analysis done by the market. All the knowledge provided will be applied in analyzing four Peruvian listed companies from different industries (cement extractor and seller, food, beverages and mining). These four companies were selected using a importance analysis, which was highly related to choose the companies with the most relevant and significant operations to the Lima Stock Exchange and the Peruvian industrial sector between 2012 and 2014.